2017
DOI: 10.21010/ajtcam.v14i4.20
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Borage Seeds Oil Against Gamma Irradiation-Induced Hepatotoxicity in Male Rats: Possible Antioxidant Activity

Abstract: Background: Borage (Borago officinal L.) is an annual herbaceous plant of great interest because its oil contains a high percentage of -linolenic acid (GLA). The present work was carried out to detect fatty acids composition of the oil extracted from borage seeds (BO) and its potential effectiveness against γ-irradiation-induced hepatotoxicity in male rats. Materials and Methods: GC-MS analysis of fatty acids methyl esters of BO was performed to identify fatty acids composition. Sixty rats were divided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
0
14
2
Order By: Relevance
“…In various studies, it was reported that irradiation caused a decrease at SOD, GSH, GSH-Px levels in the liver (Tawfik et al 2013;El-Gazzar et al 2016;Ashry et al 2017;Khattab et al 2017;Radwan and Mohamed 2018). The reduction in antioxidant enzymes is due to the depletion of enzymes during oxidative stress that occurred as a result of irradiation (Khattab et al 2017). In contrast to studies indicating a decrease in GSH in the kidneys (Ekici et al 2016;Ashry et al 2017), a significant increase in GSH levels in the kidneys and ovaries as a result of γ-radiation was observed in this study.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…In various studies, it was reported that irradiation caused a decrease at SOD, GSH, GSH-Px levels in the liver (Tawfik et al 2013;El-Gazzar et al 2016;Ashry et al 2017;Khattab et al 2017;Radwan and Mohamed 2018). The reduction in antioxidant enzymes is due to the depletion of enzymes during oxidative stress that occurred as a result of irradiation (Khattab et al 2017). In contrast to studies indicating a decrease in GSH in the kidneys (Ekici et al 2016;Ashry et al 2017), a significant increase in GSH levels in the kidneys and ovaries as a result of γ-radiation was observed in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…Increased MDA levels indicate the activation of lipid peroxidation as a result of the reaction of ROS with unsaturated free fatty acids of membrane lipids. It is known that exposure to irradiation induces liver damage (El-Gazzar et al 2016;Khattab et al 2017;Ashry et al 2017;Radwan and Mohamed 2018;). It is also reported that γ-radiation causes multiple organ dysfunction especially in the liver and an increase of MDA levels in various tissues depending on the time and dose (Simsek et al 2012;Tawfik et al 2013;Xie et al 2014;El-Gazzar et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MDA determinations ensure a good measure for peroxidation, one of the main mechanisms of cell damage causing necrosis or apoptosis (Comporti, 1985;De Ferreyra et al, 1989). It is a known fact that irradiation exposure leads to the liver damage (Khattab et al, 2017;Kilciksiz et al, 2008;Liu et al, 2007;Mansour et al, 2008). It is also stated that γradiation results in multiple organ dysfunction particularly in the liver and elevates MDA levels in various tissues based on the time and dose (Karami et al, 2018;Kilciksiz et al, 2008;Mansour et al, 2008;Simsek et al, 2012;Xie et al, 2014;).…”
Section: Discussionmentioning
confidence: 99%
“…The decreased GSH-Px activity in the tissues examined after the irradiation indicated that the first enzyme affected by the irradiation was GSH-Px. Various studies revealed that irradiation decreased SOD, GSH, and GSH-Px levels in the liver (Ashry et al, 2017;Khattab et al, 2017;Kilciksiz et al, 2008;Mansour et al, 2008;Radwan and Mohamed, 2018). The antioxidant enzymes reduced because of the depletion of enzymes during oxidative stress caused by the irradiation (Khattab et al, 2017;Mansour et al, 2008).…”
Section: Discussionmentioning
confidence: 99%